Recipe Planning Application - Abong, Angela Anak; Afip, Zehan Afizah binti (International Journal of Advanced Science Computing and Engineering, 2020)
Kenyalang’s Kitchen is an Android-based recipe planning application to promote Sarawak’s traditional recipe. The application will assist user in the preparation of customary cuisine from various ethnicities in Sarawak. The user is able to choose the recipe based on the ingredients selected. Besides that, the application provides the ‘Xprez List’ that consists of recipe list that can be prepared in a minimum time.  This application offers unique features such as‘Food Famous’ which will list all the well-known cuisine from different ethnicities in Sarawak. Another uniqueness of this application is ‘Glossary’ to help the users to understand some of the unfamiliar terms.  The recipe recommender is developed by using Object Oriented Software Development methodology. The software used is Android Studio in Java programming language. In short, the application aims to guide the users to prepare the Sarawak’s traditional recipe.